ANALYSIS OF THE DEVELOPMENT UNDERSTANDING OF THE PEOPLE BATANG TORU SUB-DISTRICT ABOUT SHARIA PAWNSHOPS - Aisyah Budi Harahap (Journal Of Sharia Banking, 2023)
The purpose of this study is the first, show the understanding of the people of Batang Toru District towards PT. Sharia pawnshop, the second is what causes the people of Batang Toru District not to use PT. Sharia Pawnshop. This type of research is qualitative research, the collection of research data is carried out by conducting observations, interviews, and documentation with research objects in Batang Toru District in South Angkola District.Based on the research obtained as follows. First, the understanding of the people of Batang Toru District towards PT. Sharia pawnshops, most of the people in the Batang Toru sub-district already know Sharia pawnshops, but the community only knows not by understanding them. The people of Batang Toru District still mostly think that at PT. Sharia pawnshops are only for pawning. The second reason people do not use Sharia pawnshops is because of the lack of understanding of the people of Batang Toru District about PT. Sharia pawnshops and lack of promotion by distributing brochures and socialization from Sharia pawnshops to the people of Batang Toru District, South Tapanuli Regency.